Impact of geometry on light collection efficiency of scintillation detectors for cryogenic rare event searches - Danevich, F; Kobychev, V; Kobychev, R; Kraus, H; Mikhailik, V; Mokina, V; Solsky, I (Elsevier, 2014)
Simulations of photon propagation in scintillation detectors were performed with the aim to find the optimal scintillator geometry, surface treatment, and shape of external reflector in order to achieve maximum light collection efficiency for detector configurations that avoid direct optical coupling, a situation that is commonly found in cryogenic scintillating bolometers in experimental searches for double beta decay and dark matter. To evaluate the light collection efficiency of various geometrical configurations we used the ZEMAX ray-tracing software. It was found that scintillators in the shape of a triangular prism with an external mirror shaped as truncated cone gives the highest light collection efficiency. The results of the simulations were confirmed by carrying out measurements of the light collection efficiencies of CaWO4 crystal scintillators. A comparison of simulated and measured values of light output shows good agreement. © 2014 Elsevier B.V. All rights reserved.